Call for Paper Information Broadcast Based on Android Application - Chan, Fenny Destasia; Handojo, Andreas; Listyani, Hanny Tabita; Aldinata, Ivan; Felicia, Felicia (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
A reliable information is a crucial thing in every event. Participants and the committee expect the fulfillment of information. In this research, writers use smartphone technology to facilitate call for paper information broadcast. The development of call for paper information broadcast application is based on the usage of Android smartphones that are relatively popular device to be used by the people in this era. On this application, there are some features that can facilitate the users to get the best reading experience. This application also grants the committee some rights to manage the event through website. The design and development of this application are going through three phases. Analysis, interface design, and code writing. The website is based on HTML 5 and the mobile application is based on Ionic Framework for smartphone application based on Android, and MySQL as database manager and also a test conducted through automatic email, SMS gateway, and push notification on smartphone. In this research, a call for paper application was developed to facilitate information broadcast. The application helps the participants to get information through SMS, notification, and email from their smartphone. After going through the testing process, this application can run their features inside the application smoothly.